Analysis of Curriculum and Textbook of Pancasila and Civic Education in State High School Madani Palu Integrated Model - Sukmawati Sukmawati; Shofia Nurun Alanur; Jamaludin Jamaludin; Kiki Rinawati; Nelfi Nelfi; Jihan Fatihah; Putri Sabina; Febriani Febriani; Alnawati Alnawati; Grasia Eirene Dimba Yelvita Dimba; Anggriani Lagonda; Riska Maharani; M. Shanda Saputra; Agios Tangkuman (CV. Rayyan Dwi Bharata, 2023)
This study aims to find out how to use the curriculum and analysis of PPKn textbooks in the Madani Integrated Model Public High School by using the method of observation and interviews with PPKn teachers who are also vice principals of student affairs with a descriptive research type. The results of the study (1) The curriculum used in this school has undergone 3 changes, namely the Competency-Based Curriculum (2004) where students are required to be able to participate actively for the formation of a graduate profile. The 2006 Education Unit Level Curriculum (KTSP) conveys curriculum messages to students to shape their competencies according to their characteristics and abilities, and the 2013 Curriculum (K13) requires teachers to be active in creating and growing activities according to the programmed plans. (2) The textbooks used and those analyzed were the 2017 Edition of Pancasila and Citizenship Education for class X (Ten) which were also equipped with pictures of each material. The use of textbooks in Civics learning activities in class is very good so this indicates that students are more interested in using textbooks than not using textbooks in learning activities.